Improving Customer Loyalty of Batik Yoga Art in Semarang - Susetyo Darmanto; Rachmah Dewi Larasatie (Universitas Muhammadiyah Semarang, 2025)
This research aims to determine how Batik Yoga Art customer loyalty in Semarang is influenced by brand equity and product quality. The population of this study consisted of 100 respondents, and the sampling techniques used were quota and accidental sampling. The data source comes from primary data, which was collected through a questionnaire. The data is analyzed using multiple linear regression. The finding shows that brand equity has a positive and significant impact on customer loyalty. Further results also show that product quality has a positive and significant impact on customer loyalty. The implication suggests that Batik Yoga Art enhances innovative product esthetic with more interesting and up-to-date trends.